A study on clinico-epidemiological profile of scrub typhus in rural Bengal and therapeutic response to known drugs - Pandey, Gopal (International Journal Of Community Medicine And Public Health, 2022)
Background: Scrub typhus is an important cause of fever in South and East Asia and the Pacific, but is grossly underdiagnosed due to lack of awareness. This was a prospective observational study to study the clinical profile of scrub typhus in paediatric population in a tertiary care hospital in Rural Bengal of Malda district. Methods: The study was conducted from May 2021 to November 2021 among children presenting to OPD and admitted in IPD of Malda Medical College and Hospital in the Deparment of Paediatrics. Children under the age of 12 years presenting with signs and symptoms suggestive of scrub typhus were included in this study and serological diagnosis was confirmed by Scrub IgM ELISA with a positive titre >0.5. Results: Out of the 178 cases enrolled in our study, 136 were confirmed positive by ELISA. All the cases were admitted with fever (100%), other symptoms were vomiting (77.9%), cough (68.3%), abdominal pain (57.3%), maculopapular rash (52.9%), headache (49.2%), myalgia (41.1%), oedema (30.8%), conjunctival congestion (23.5%). Hepatomegaly (91.1%), splenomegaly (83.8%) and lymphadenopathy (75%) were the most common signs. Oral doxycycline in doses of 5 mg/kg/day in 2 divided doses were given in half the cases (68) and azithromycin (10 mg/kg/day) were given in 34 cases, while 34 cases were given oral chloramphenicol (75 mg/kg/day). Doxycycline and chloramphenicol were equally effective with defervescence in maximum cases within 48 hrs. Azithromycin response was poor with fever persisting in 80% cases after 48 hrs. Conclusions: Scrub typhus must be included in the differential diagnosis of acute febrile illness in children with or without eschar for its early detection and prompt treatment leading to favourable outcome. Doxycycline or Chloramphenicol were equally effective in treatment while Azithromycin showed poor response.